PENGARUH KOMPETENSI SDM, IMPLEMENTASI SISTEM KEUANGAN DESA, SISTEM PELAPORAN TERHADAP AKUNTABILITAS - Ni Komang Novita Sari; Kadek Dewi Padnyawati; Ni Putu Yeni Yuliantari (UNHI Press, 2022)
The paper compiled in this study aims to prove the relationship that exists between the capabilities of HR, Siskeudes, and reporting system systematics and accountability. All village officials who work in the Village Office in Gianyar Regency as many as 12 villages are made into the population. The sample used in this study was 36 people who were determined by the non-probability sampling method. The results of this study indicate that the accountability of village fund management will be influenced by the state of Human Resource Competence, Siskeudes, and Reporting Systems.